QUALITY DETERMINANT OF ACCOUNTING INFORMATION FOR PRIVATE UNIVERSITIES - Eka Putri, Meirina Alkhoiriah (Journal of Economic Development, Environment and People, 2021)
Abstract. The aim of this study is to determine the impact on the quality of accounting information of organizational culture, organizational commitment, internal control, the quality of accounting information systems, and leadership style. This study used primary data and a purposive sampling method to analyze a sample of 202 individuals who are involved in college finance. The research method used is a quantitative analysis with the use of multiple regression methods. The results are: (1) Organizational culture, internal control, and the quality of accounting information systems all have a positive and significant impact on the quality of accounting information; (2) organizational commitment and leadership style both have a positive but insignificant impact on the quality of accounting information systems. Keywords: Organizational culture, organizational commitment, internal control, Accounting Information Systems, leadership style, Accounting Information